(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the effects of different stocking densities on the performance, eggshell quality, surface body temperature and hematological parameters of Japanese laying quails based on physiological indicators of animal welfare. Two hundred and thirty seven-week-old Japanese quails were used in this experiment. The quails were completely randomized to four stocking densities: 112.2 (T1), 102 (T2), 93.5 (T3), and 86.31 (T4) cm²/quail and five replicates each. Hematological parameters were analyzed as a 4x4 factorial design (stocking density X time) over four periods of blood sampling (25, 50, 75, and 100 days). To obtain the body surface temperature (Ts, °C) three thermograms (head, core and shin) were captured from each repetition per plot (2 repetitions per experimental plot) every 25 days (25, 50, 75, and 100 days). Feed intake, feed conversion per egg mass, feed conversion per dozen eggs, egg mass, egg production rate, and eggshell quality-related variables were not affected by treatments. However, egg weight (p = 0.023) and core temperature (p = 0.003) were influenced by different cage stocking densities. The heterophil/lymphocyte ratio increased (p = 0.01) with increasing time and stocking density. The mean corpuscular volume (p = 0.0001) as well as the total leukocyte count (p = 0.001) increased until the third blood sampling period (75 days) and then decreased in the last period. Different stocking densities do not interfere with the performance and eggshell quality of Japanese quails. However, the hematological parameters and head temperature are affected by different cage stocking densities and time.